Evidence of vortex-induced lift on a yawed wing in reverse flow. (September 2014) - Raghav, Vrishank; Mayo, Michael; Lozano, Rafael; Komerath, Narayanan
Rotating blades on helicopters experience reverse flow under high advance ratio conditions. Here, reverse flow is characterized by the flow traveling from the sharp trailing edge to the blunt leading edge. Uncertainty in the blade aerodynamic loads under these conditions has been a limitation during the design of high-speed rotorcraft. In this work, we hypothesize that the reverse flow over a yawed blade includes phenomena similar to the formation of a leading edge vortex on sharp-edged delta wings. Low-speed wind tunnel experiments are reported on a scaled version of a rotor blade in regular and reverse flow over a large range of yaw and moderate ranges of angle of attack. Force measurements indicate a deviation from yawed-wing expectations at high yaw angles. Surface flow visualization via tufts shows the existence of an attached span-wise vortex on the wing.